1983
DOI: 10.1007/bf00282705
|View full text |Cite
|
Sign up to set email alerts
|

Control of pulsatile insulin secretion in man

Abstract: Plasma insulin and glucose concentrations were examined in man in a basal state from central venous samples taken at 1-min intervals for up to 2.5 h. Normal subjects have insulin oscillations of mean period 14 min (significant autocorrelation, p less than 0.0001) with changes in concentration of 40% over 7 min. The pulsation frequency was stable through cholinergic, endorphin, alpha-adrenergic or beta-adrenergic blockade, or small perturbations with glucose or insulin. Stimulation of insulin secretion by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 22 publications
7
127
0
2
Order By: Relevance
“…The presence of preserved pulsatile insulin secretion after pancreas transplantation, albeit at increased frequency, further indicates the presence of an intra-pancreatic coordinating mechanism [75]. In vivo, cholinergic, alphaadrenergic and beta-adrenergic blocking agents did not perturb the detected periodicity in humans [131] or in monkeys [76], thus failing to support significance of these receptors on controlling pulsatile insulin release in vivo.…”
Section: Contribution Of Pulsatile Insulin Release To the Overall Insmentioning
confidence: 98%
See 2 more Smart Citations
“…The presence of preserved pulsatile insulin secretion after pancreas transplantation, albeit at increased frequency, further indicates the presence of an intra-pancreatic coordinating mechanism [75]. In vivo, cholinergic, alphaadrenergic and beta-adrenergic blocking agents did not perturb the detected periodicity in humans [131] or in monkeys [76], thus failing to support significance of these receptors on controlling pulsatile insulin release in vivo.…”
Section: Contribution Of Pulsatile Insulin Release To the Overall Insmentioning
confidence: 98%
“…In addition, the overall insulin secretion could be regulated by nerve blockers [76,131] and neurotransmitters such as galanine [134], epinephrine [135,136], GABA [137] dopamine [138], as well as nitric oxide [139], and because overall insulin release is pulsatile, the impact of these agents is probably involved in the regulation of pulses, although they have not been studied. In addition, sensory nerve blocking markedly increases insulin release [140], suggesting an inhibitory role of sensory nerves, and this could explain the loss of auto-feedback inhibition of insulin on insulin release in humans with pancreas transplant [141].…”
Section: Contribution Of Pulsatile Insulin Release To the Overall Insmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose concentrations oscillate on a minute-by-minute basis (Abdallah et al, 1997), driven, at least in part, by the pulsatile nature of insulin secretion (Matthews et al, 1983). Presumably, the oscillations of plasma glucose in different tissues in the body are not in phase with each other, because it takes different lengths of time for the pulses of insulin from the pancreas to reach them.…”
Section: Glycaemic Index Interlaboratory Study Tms Wolever Et Almentioning
confidence: 99%
“…in plasma glucose and reflect a pacemaker function of the pancreas (Lang et al, 1981;Matthews et al, 1983a). Studies in normal subjects with suppressed endogenous insulin secretion and diabetic patients have indicated that less insulin is required to maintain normoglycaemia if the hormone is infused in an oscillatory manner compared to a constant rate (Matthews et al, 1983b;Bratusch-Marrain et al, 1986;Matthews et al, 1987;Paolisso et al, 1988a;Paolisso et al, 1988b).…”
mentioning
confidence: 99%